Thermal Characterisation and Toxicity Profile of Potential Drugs from a Class of Disubstituted Heterofused Triazinones - Małgorzata Sztanke; Renata Łyszczek; Agnieszka Ostasz; Halina Głuchowska; Krzysztof Sztanke (Molecules)
The thermal characterisation and toxicity profile of a class of disubstituted heterofused triazinones were revealed in this article for the first time. The thermal behaviour of molecules 1–12 was investigated by means of TG and DSC analyses performed in an air atmosphere and by the coupled TG/FTIR technique in a nitrogen atmosphere. The heating atmosphere affects both the stability of compounds and the degradation mechanism. A two-step degradation occurs in air, while a one-step degradation takes place in nitrogen, both preceded by a melting process. Compound 3 shows the highest thermal stability, while molecule 10—the lowest. The thermal decomposition of the studied heterocyclic molecules begins with the degradation of the bicyclic system, resulting in the formation of volatile gaseous products such as ammonia/hydrazine, hydrogen cyanide, carbon dioxide, and isocyanates. In the further stage, mainly aromatic compounds are released, and their chemical composition depends on the presence and type of substituents at the phenyl and benzyl moieties. In addition, the toxicity profiles of molecules were assessed in the animal (zebrafish) and cellular (erythrocytes) models, and the antihaemolytic activity was evaluated in the AAPH- and H2O2-induced haemolysis inhibition assays. It was found that all the tested compounds are safe for the developing zebrafish and red blood cells, and they are able to effectively protect erythrocytes from oxidative damage. These favourable properties make them promising drug candidates suitable for further in vivo studies.